Effects of Platelet Rich Plasma in Combination with Hyaluronic Acid in the Treatment of Primary Knee Osteoarthritis (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Platelet Rich Plasma (PRP) is increasingly applied in clinical practice to treat knee degenerative pathology. Both PRP and hyaluronic acid (HA) have been extensively used to improve lubrication, modulate inflammation and modify the catabolic micro-environment of the joint.Objective: This study was aimed to evaluate the potential synergistic effects of PRP in combination with hyaluronic acid in primary knee osteoarthritis.Methodology: This randomized control trial was carried out on adult patients with primary knee osteoarthritis who attended the Pain Clinic of Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh, during the period of September 2015 to August 2017. The patients were randomly assigned to one of the two groups designated as group P (control group) who were only treated with PRP and group PH (experimental group) who were treated with the combination of PRP and hyaluronic acid. After providing the allocated treatment, all patients were undergone follow-up examination at 1st week, 1st month and 3rd month for pain improvement by VAS scale and for functional improvement by International Knee Documentation Committee (IKDC) score.Results: A total number of 34 patients were recruited for this study. Visual analogue score 1st month (5.85±0.83) and 3rd month (3.01±0.12) follow up showed statistically significant difference among two group (p=0.001). Inter group comparison showed that, mean VAS score of group PH (3.01±0.12) decreased more than Group P (4.01±1.01). In case of functional improvement, group PH also showed statistically better improvement during 1st month (45.76±3.25) and 3rd month (62.06±5.37) follow up than Group P.Conclusion: In conclusion articular platelet rich plasma in combination with hyaluronic acid provide better pain relief and improvement of functional status than PRP therapy alone in primary knee osteoarthritis.Journal of National Institute of Neurosciences Bangladesh, 2019;5(2): 137-142